Transmetallations between aryltrialkyltins and borane: Synthesis of arylboronic acids and organotin hydrides - Faraoni, María Belén (2000)
Aryltrialkyltin compounds react with borane in THF to give mixtures of trialkyltin hydrides and arylboranes, which on hydrolysis give arylboronic acid in high yields. The arylboronic acids are easily separated and obtained free of organotins.